Open areas associated with traditional agriculture promote functional connectivity among amphibian demes in Mediterranean agrosystems - Albero, Luis; Martínez-Solano, Íñigo; Hermida, Miguel; Vera, Manuel; Tarroso, Pedro; Bécares, Eloy (Landscape ecology, 2023)
Context Functional connectivity across fragmented habitat patches is essential for the conservation of animal populations in humanized landscapes. Given their low dispersal capacity, amphibians in the Mediterranean region are threatened by habitat fragmentation and loss due to changes in land use, including agricultural intensification. Objectives We assessed patterns of functional connectivity of a Near Threatened Mediterranean amphibian, the sharp ribbed newt ( Pleurodeles waltl ), in an agricultural landscape matrix in NW Spain subject to different intensification regimes. Methods We sampled newts in 17 ponds embedded in a terrestrial habitat matrix dominated by agricultural land uses. Genome-wide molecular markers (1390 SNPs) were used to assess patterns of genetic diversity and gene flow among ponds. We tested the role of landscape features on functional connectivity using isolation by resistance models incorporating information on Normalized Difference Vegetation Index (NDVI) data. Results We found low levels of genetic diversity in all sampled populations. Global F ST estimates and cluster analyses revealed shallow but significant genetic structure in the study area, with NDVI-based resistance models showing that open areas (rainfed crops and grasslands) offer lower resistance to gene flow and thus promote functional connectivity among demes. Conclusions Our study highlights the important role of landscape features, such as open areas resulting from traditional rainfed agriculture, in promoting functional connectivity between amphibian populations in Mediterranean agrosystems. Conservation policies must adopt a functional network strategy and protect groups of inter-connected temporary ponds across the traditional agricultural matrix to efficiently preserve their associated biotic communities.